Analisis Al-Musytarak Al-Lafzi Kata Hisāb Dan Derivasinya Dalam Surat An-Nūr Serta Implikasinya Terhadap Pemahaman Tafsir - M. Ripani Saputra; Angga Frananda; Muhammad Azhar; Muhammad Sayuti; Mudiul Hayat Pasaribu; Mhd Nopendri Saputra; Rudi Edwaldo Jasmit (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The Qur'an as the central text in Islam has extraordinary linguistic richness, one of which is the phenomenon of al-musytarak al-lafzī (polysemy), where one lafaz has various meanings. This study aims to deeply analyse the meanings of the lafaz hisāb and its derivations that are classified as al-musytarak al-lafzī in Surah An-Nūr. The focus of the study is on verses 11, 15, 39, and 57, to identify variations in meaning based on the context of the verse (siyāq al-āyah) and its implications for interpretive understanding. The method used is qualitative-descriptive with a semantic analysis approach and library research. The primary data source is the Qur'an, supported by classical and contemporary tafsir books, Arabic dictionaries, and related scientific literature. The results show that the lafaz hisāb and its derivations in Surat An-Nūr (such as tahsabūnahu, yahsabuhu, tahsabanna) have at least three main variants of meaning: (1) presumption (ظَنٌّ), (2) simile (مَثَلٌ), and (3) thinking (فِكْرٌ). This difference in meaning significantly affects the interpretation of the verse and the message it contains. An accurate understanding of al-musytarak al-lafzī is crucial to avoid misunderstandings in interpreting the Qur'ān and is relevant to the development of Qur'ānic linguistic studies. Translated with DeepL.com (free version)